Спекание алмазных нанопорошков различного генезиса при высоком давлении - Назарчук, С.Н.; Бочечка, А.А.; Романко, Л.А.; Гвяздовская, В.Л. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
Formation of diamond polycrystals by high pressure – high temperatures action on diamond nanopowders of various genesis is described. It is shown, that polycrystals sintered from a powder synthesized by great dispatch-wave processing of graphite have the highest values of density and wear resistance.